Perforated Colonic Peritonitis As A Source Of Surgical Sepsis - Okhunov Alisher Oripovich (International Journal of Medical Science and Public Health Research, 2026)
Background. Perforated colonic peritonitis remains one of the most severe conditions in emergency abdominal surgery and is frequently complicated by surgical sepsis. Despite radical elimination of the perforation source, systemic deterioration may develop rapidly or follow a subacute course, particularly in patients with significant comorbidity. Methods. A retrospective cohort study included 118 patients operated on for perforated colonic peritonitis of malignant and non-malignant etiology. Surgical sepsis was defined according to Sepsis-3 criteria. Clinical course, comorbid conditions, surgical strategy, need for intensive care, progression to septic shock and multiple organ failure, and in-hospital mortality were analyzed. Results. Surgical sepsis was identified in a substantial proportion of patients either at admission or during early postoperative period. Patients with pronounced comorbidity more often demonstrated fulminant septic progression with early development of septic shock, multiple organ failure, and high mortality, despite radical surgical source control. In patients without severe comorbidities, septic complications frequently evolved in a subacute manner, with transient postoperative stabilization that could mask ongoing systemic infection. Requirement for intensive care treatment and progression to septic shock were strongly associated with adverse outcomes. Conclusion. Perforated colonic peritonitis should be regarded as a condition with an inherent risk of surgical sepsis regardless of the apparent adequacy of operative management. Apparent postoperative stabilization does not exclude systemic progression. Continuous assessment for septic manifestations and timely escalation of anti-septic therapy are essential to improve outcomes in this high-risk patient population.